Pengaruh Likuiditas, Leverage, Profitabilitas, dan Sales Growth Terhadap Financial Distress pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2018-2020 - Hastin Ari Kusuma; Maya Widyana Dewi; Suhesti Ningsih (Jurnal Akuntansi dan Pajak, 2022)
Financial distress is defined as the stage of declining financial condition of a company that begins with the inability of a company to pay off its debts, if this condition is not handled immediately and even gets worse, it will cause the company to go bankrupt. The purpose of this study is to investigate the influence of liquidity, leverage, profitability, and sales growth toward financial distress either simultaneously or partially. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The sampling method used is purposive sampling. There are 66 samples in this study. The data analysis used is logistic regression by using SPSS version 23. The results of this study prove that liquidity, leverage, profitability, and sales growth simultaneously affect financial distress. Partially, profitability and sales growth have an effect on financial distress, while liquidity and leverage have no effect on financial distress.